Internalization of Islamic Religious Education Values in Forming Students' Self-Control Towards Online Game Use in Grade IV Students - Halimatus Sa'diya; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
The use of online games among elementary school students has the potential to affect students’ behavior and self-control if not properly managed. Islamic Religious Education plays an important role in shaping students’ character and self-regulation through the internalization of religious values. This study aims to describe the internalization of Islamic Religious Education values in shaping students’ self-control toward the use of online games among fourth-grade students at SDI Hidayatul Ummah, Pakuniran District, Probolinggo. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. Research informants included Islamic Religious Education teachers, the school principal, students, and parents as supporting informants. Data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through source triangulation. The findings indicate that the internalization of Islamic Religious Education values is implemented through contextual learning, role modeling, and habituation of religious behavior. Values of discipline and responsibility contribute to students’ ability to control their use of online games. The internalization of Islamic Religious Education values contributes to strengthening students’ character and self-control in facing the influence of digital technology development.